2010
DOI: 10.1007/s11160-010-9178-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating asymmetry and exogenous stress in fishes: a review

Abstract: Fluctuating asymmetry (FA), which has been examined in a variety of plants and animals, is widely promoted as a useful bioindicator of exogenous stressors in habitats, whether of natural or anthropogenic origin. Wildlife managers and researchers often use a specific group of organisms as an indicator of the health of a given habitat. The purpose of this review is to demonstrate that FA can be an effective fish biomonitoring tool by presenting a vote counting meta-analysis of 81 fish FA studies published betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 138 publications
(222 reference statements)
0
60
0
Order By: Relevance
“…However, water chemistry may have a more direct influence on FA and may be a more powerful predictor of developmental stress. Other factors such as nutrition, chemical contaminants and pH have also been shown to increase FA (Allenbach, 2011). Annual variability in temperature and water levels could also impact a variety of stressors contributing to increase variability among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, water chemistry may have a more direct influence on FA and may be a more powerful predictor of developmental stress. Other factors such as nutrition, chemical contaminants and pH have also been shown to increase FA (Allenbach, 2011). Annual variability in temperature and water levels could also impact a variety of stressors contributing to increase variability among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We selected and quantified five paired bilateral characters (Figure 4) that are dichotomous and conserved between Lepomis species [27]. Preliminary results showed no significant responses and almost no variability in the FA of meristic characters among creeks.…”
Section: Metric and Meristic Analysesmentioning
confidence: 99%
“…Metric characters were measured to the nearest ±0.01 mm in triplicate on three different days allowing for assessment of measurement error (ME) [4]. [27] were selected and quantified. Meristic characters: (1) pored lateral line scales; and (2) pelvic fin rays were not used in analyses.…”
Section: Metric and Meristic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…FA has generated interest among population biologists because it reflects one of the components of fitness-developmental stability, i.e., the ability of an organism to consistently produce an "ideal" phenotype in a given environment [5]. Although an association between FA and fitness is not always observed in empirical studies, recent reviews concluded that, overall, FA can be considered a useful tool for assessing a population's average fitness [6][7][8].…”
Section: Introductionmentioning
confidence: 99%